高蛋白脱酚棉籽粕制取工艺研究Preparation of high protein degossypoled cottonseed meal - 王如南1,2，张扬3，韩文杰2,3 WANG Runan1,2, ZHANG Yang3, HAN Wenjie2,3 (Zhongguo youzhi)
为了满足市场需求，提升棉籽粕利用价值，结合实际生产情况，采用单因素控制变量法，调整生产工艺中关键控制参数如原料棉仁中的含壳率、甲醇溶液萃取工艺参数以及成品粉碎筛分条件等，确定了分别以含壳率为2%和5%的棉仁为原料的高蛋白脱酚棉籽粕生产工艺。当原料含壳率为2%时，适宜的萃取工艺为浸泡萃取,料液比1∶ 3,浸泡萃取脱酚时间 30 min，甲醇溶液萃取梯度60%-70%-80%-90%，共萃取4次，残油控制在0.7%以下，蒸脱烘干控制水分在5%以下。原料含壳率为5%时，适宜的萃取工艺为淋液萃取，料液比1∶ 2，甲醇溶液萃取梯度70%-70%-70%-70%-80%-90%，共萃取6次，残油控制在0.7%以下，蒸脱烘干控制水分在5%以下。采用上述两种方法，可得到粗蛋白质含量在70%以上、游离棉酚含量满足企业内控指标要求（≤400 mg/kg）的脱酚棉籽粕。 To meet the market demand, enhance the utilization value of cottonseed meal,combined with the actual production situation, the single factor variable control method was used to adjust the key control parameters, such as the shell content of cottonseed kernel, methanol solution extraction process parameters and the cracking and screening conditions of finished products, to determine the production process of high protein degossypoled cottonseed meal using cottonseed kernel with 2% and 5% shell content as material. When the shell content of the raw material was 2%, the appropriate extraction process was soak extraction, material-liquid ratio 1∶ 3, soak extraction time 30 min, methanol solution extraction gradient 60%-70%-80%-90%,extraction times 4, the residual oil of cottonseed meal below 0.7%, and the moisture after desolventing and drying below 5%. At 5% shell content,the appropriate extraction process was liquid-liquid extraction, material-liquid ratio 1∶ 2, methanol solution extraction gradient 70%-70%-70%-70%-80%-90%, extraction times 6, the residual oil of cottonseed meal below 0.7%，and the moisture after desolventing and drying below 5%. Using these two methods, degossypoled cottonseed meal with crude protein content above 70% can be obtained with content of free gossypol meeting the requirements of internal control index (≤400 mg/kg).